Overview of Forecasting Zakat Collection in Indonesia Using Multiplicative Decomposition - Salman Al Parisi (International Journal of Zakat, 2017)
Social welfare can be achieved if high economic growth can reduce a country’s poverty, accompanied by a decrease in the value of gini coefficient. Zakat is one of the primary instruments of economic philanthropy in Muslim countries, faciliatating redistribution of wealth and income. Zakat potential in Indonesia has reached Rp 286 trillion, but the actual zakat collection only reached 3.7 trillion in 2015. This study aims to determine the following: (1) the forecasting of zakat collection in Indonesia based on the historical data for the next 5– 10 years or over time and (2) the system used by Muslim countries to collect zakat fund. This study used the multiplicative decomposition forecasting method with annually data collected over 2005-2015. The findings showed that zakat collection would be expected to reach about Rp 5.0 trillion in 2020. It is expected to increase to 8.33 trillion in 2029, with mean absolute percent error (MAPE) value as much as 0.18. Furthermore, there are different kinds of zakat systems used by Muslim countries. Indonesia uses the voluntary zakat system, which could affect the amount of zakat collection. The findings of this study are expected to inform policy makers regarding the management of zakat collection. Keywords: Forecasting, Zakat Collection, Poverty Eradication, Multiplicative Decomposition